2013
DOI: 10.1016/j.biocon.2013.08.034
|View full text |Cite
|
Sign up to set email alerts
|

The effects of habitat degradation on metacommunity structure of wood-inhabiting fungi in European beech forests

Abstract: +358-40-8204799 AbstractIntensive forest management creates habitat degradation by reducing the variation of forest stands in general, and by removing old trees and dead wood in particular. Nonintervention forest reserves are commonly believed to be the most efficient tool to counteract the negative effects on biodiversity, but actual knowledge of the conservation efficiency is limited, especially for recent reserves. The structure of ecological communities is often described with measures of nestedness, beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 48 publications
(52 reference statements)
0
25
0
Order By: Relevance
“…Hence, the forest landscape of continental Europe provides an interesting case to investigate the long-term effects of habitat fragmentation on wood-inhabiting fungi. Nevertheless, only few large-scale studies have been conducted in this area (Ódor et al, 2006;Halme et al, 2013;Heilmann-Clausen et al, 2014a), and none of these have focused specifically on the effects of habitat loss and fragmentation. Furthermore, a previous study which attempted to measure isolation effects in a beech forest landscape, failed to do so conclusively because of the small scale of the study .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hence, the forest landscape of continental Europe provides an interesting case to investigate the long-term effects of habitat fragmentation on wood-inhabiting fungi. Nevertheless, only few large-scale studies have been conducted in this area (Ódor et al, 2006;Halme et al, 2013;Heilmann-Clausen et al, 2014a), and none of these have focused specifically on the effects of habitat loss and fragmentation. Furthermore, a previous study which attempted to measure isolation effects in a beech forest landscape, failed to do so conclusively because of the small scale of the study .…”
Section: Introductionmentioning
confidence: 98%
“…Wood-inhabiting fungi are confined to ephemeral habitats (decomposing dead wood units) and organized as habitat-tracking metacommunities (Halme et al, 2013), which makes them especially sensitive to habitat loss and fragmentation (Stokland et al, 2012). For wood-inhabiting organisms, habitat loss and fragmentation can be assessed at two levels; at the overall habitat level corresponding to the forest area and at the resource level, corresponding to the amount of dead wood present in the forest.…”
Section: Introductionmentioning
confidence: 99%
“…Despite such uncertainty, heterogeneity of forest structure in terms of tree species composition, age structure, and size distribution of live trees and dead wood has been identified as the most important stand-level factor affecting cryptogam diversity (Ódor et al, 2006;Ellis, 2012;Halme et al, 2013;Sverdrup-Thygeson et al, 2014). In particular, the effects of forest age, large old trees, and dead wood on cryptogam diversity have been repeatedly emphasized (e.g., Fritz et al, 2008;Ranius et al, 2008;Lindenmayer et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Our main objective was to identify the quantitative limits of forest structural attributes that affect cryptogam diversity along a gradient of forest management practices in central Europe. We hypothesized that cryptogam diversity is related to forest structure at the stand scale and that suitable structures form the basis for the metapopulation structure of cryptogams in European forests (Löbel et al, 2006;Halme et al, 2013). Such studies are needed to develop recommendations for future forest management and for implementing these practices.…”
Section: Introductionmentioning
confidence: 99%
“…Different species depend on different successional stages, including old growth (structurally complex forests dominated by large old trees) as well as structurally complex early seral stands (those following severe canopy-opening disturbances) (e.g. Halme et al, 2013;Lehnert et al, 2013;Sippola, 2001;Swanson et al, 2014). This landscape-scale gamma diversity, and the continuity of habitats over broad scales, is equally relevant as the stand-scale differences in alpha diversity that Schulze et al (2014) reported.…”
Section: Limited Scopementioning
confidence: 89%